2007
DOI: 10.1165/rcmb.2006-0270oc
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil Factor Family 3 Peptide Promotes Human Airway Epithelial Ciliated Cell Differentiation

Abstract: Human airway surface epithelium is frequently damaged by inhaled factors (viruses, bacteria, xenobiotic substances) as well as by inflammatory mediators that contribute to the shedding of surface epithelial cells. To regain its protective function, the epithelium must rapidly repair and redifferentiate. The Trefoil Factor Family (TFF) peptides are secretory products of many mucous cells. TFF3, the major TFF in the airways, is able to enhance airway epithelial cell migration, but the role of this protein in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…Mucus hypersecretion and goblet cell metaplasia are important traits of asthma, also linked with IL-13 dysregulation. We also noticed that TFF3, which is expressed in mucous cells and can promote the differentiation of ciliated human airway epithelial cells [21], was up-regulated in allergic patients. This illustrates the complexity of the mechanisms leading to abnormal repair and remodelling.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Mucus hypersecretion and goblet cell metaplasia are important traits of asthma, also linked with IL-13 dysregulation. We also noticed that TFF3, which is expressed in mucous cells and can promote the differentiation of ciliated human airway epithelial cells [21], was up-regulated in allergic patients. This illustrates the complexity of the mechanisms leading to abnormal repair and remodelling.…”
Section: Discussionmentioning
confidence: 67%
“…This group puts together important markers of multiciliogenesis (PLK4 and CDC20B) [12] and molecules associated with asthma in genomewide analyses (GSDML and CYFIP2). A second group, which includes POSTN, SPINK5, CD44, TFF3, ITLN1, FOXA3 and SPDEF, was clearly associated with basal or mucous cells [21]. Most of them were decreased during in vitro differentiation while all were up-regulated in patients with uncontrolled asthma.…”
Section: Control Of Asthma Affects Gene Expression Signature Of Nasalmentioning
confidence: 96%
“…Using a murine asthma model it was shown that trans-differentiating Clara cells specifically express TFF1, which is stored in a specific subset of secretory granules [47]. These points to a role for TFF1 as an autocrine factor for the transdifferentiation of Clara cells toward goblet cells [47]. It is demonstrated that induction of TFF3 synthesis was shown with differentiation in vivo humanized tracheal xenograft and in vitro air-liquid interface culture models.…”
Section: Goblet Cell Metaplasia From Clara and Ciliated Cellsmentioning
confidence: 99%
“…Goblet cells are derived, at least in part, from Clara cells, which trans-differentiate from a serous into a mucous phenotype. Using a murine asthma model it was shown that trans-differentiating Clara cells specifically express TFF1, which is stored in a specific subset of secretory granules [47]. These points to a role for TFF1 as an autocrine factor for the transdifferentiation of Clara cells toward goblet cells [47].…”
Section: Goblet Cell Metaplasia From Clara and Ciliated Cellsmentioning
confidence: 99%
“…Human bronchial epithelial cells (HBECs) were isolated from human normal bronchial tissues from patients undergoing surgery Clin Exp Metastasis for bronchial carcinoma and were cultivated as described previously [19]. Human lung cell lines Calu-3, 16HBE, BEAS-2B, and BZR were grown in Dulbecco's modified Eagle's medium (DMEM) (Gibco, Invitrogen, Carlsbad, CA, USA) supplemented with 10 % fetal calf serum (Gibco), and 100 UI/mL of penicillin and streptomycin (Gibco), and HBE4-E6/E7 (HBE4) in keratinocyte serum free medium (Gibco) supplemented with 0.2 ng/mL EGF (epidermal growth factor) and 25 lg/mL BPE (Bovine pituitary extract).…”
Section: Tumor Cell Linesmentioning
confidence: 99%